Break the cycle a guide to healing intergenerational trauma - Buque, Mariel (New York Dutton, 2024)
"The definitive, paradigm-shifting guide to healing intergenerational trauma-weaving together scientific research with practical exercises and stories from the therapy room-from Dr. Mariel Buque, PhD, a Columbia University-trained trauma-informed psychologist and practitioner of holistic healing"--
From Dr. Mariel Buque, a leading trauma psychologist, comes this groundbreaking guide to transforming intergenerational pain into intergenerational abundance. With Break the Cycle, she delivers the definitive guide to healing inherited trauma. Weaving together scientific research with practical exercises and stories from the therapy room, Dr. Buque teaches readers how trauma is transmitted from one generation to the next and how they can break the cycle through tangible therapeutic practices, learning to pass down strength instead of pain to future generations.
Sensitivity acknowledgement -- A note about professional emotional help -- Part I: What you inherited -- You are a cycle breaker ; Your intergenerational higher self ; Your body remembers your trauma ; Unhealed trauma and you ; A genetic inheritance ; Part II: There are layers to this -- Your intergenerational nervous system ; Your intergenerational inner child ; Intergenerational cycles of abuse ; When collective trauma enters your home ; Part III: Alchemizing your legacy -- Grieving your traumatic lineage ; Embodying generational resilience ; Leaving a generational legacy ; Epilogue.
Includes bibliographical references (pages 251-264) and index.
112874
Keywords: Generational trauma -- Treatment; Families -- Mental health; Psychic trauma -- Treatment; Holistic medicine; Self-help publications